COMPARATIVE ANALYSIS OF CHEMICAL COMPOSITION AND SPECTRAL PROPERTIES OF BIOCHAR PRODUCED FROM PIGEONPEA AND COTTON RESIDUES - K.C. NATARAJA*, D. BALAGURAVAIAH, CH. SRINIVASA RAO, T. GIRIDHARA KRISHNA, Y. REDDI RAMU and P. LAVANYA KUMARI (The Journal of Research ANGRAU, 2021)
The study was conducted during 2018-19 to characterize the biochar. Biochar from two differentagricultural crop residues viz., pigeonpea (Cajanas cajan (L.) Millsp.) and cotton (Gossypium spp)were produced under the slow pyrolysis process and studied for their physico-chemical properties,carbon stability, recovery and spectral properties. The proximate analysis of biochars recorded higherbiochar yield (24.5%), higher fixed carbon (63.84%), lower volatile matter (5.85%) and ash (16.2%)in pigeonpea compared to cotton biochar (yield 22.6%; fixed carbon 62.69%; volatile matter 6.90%;and ash 18.5%). The pH of biochar from pigeonpea and cotton was 9.86 and 9.82, respectively.Electrical conductivity (EC) values of biochar from pigeonpea and cotton are 2.04 and 2.53 dS m-1,respectively. The nutrient concentration of derived biochar indicates enrichment of carbon and depletionof nitrogen and other nutrient elements after slow pyrolysis process. The pigeonpea biochar hadlower bulk density (0.26 g cm-3) compared to cotton biochar (0.29 g cm-3). The CEC of pigeonpea andcotton biochar is 44.33 and 33.86 cmol (P+) kg-1, respectively; the carbon recovery level after conversionof the pigeonpea and cotton residues to biochar was 27.6 and 29.0 %, respectively. The typicalhoney-comb like structure of pigeonpea biochar analysed through SEM micrographs revealed therelatively porous nature of pigeonpea biochar. The study demonstrates that both pigeonpea andcotton biochars are substantially different despite being produced under the same slow pyrolysisprocess.